If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -106 + -8x = 10x + 20 Reorder the terms: -106 + -8x = 20 + 10x Solving -106 + -8x = 20 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -106 + -8x + -10x = 20 + 10x + -10x Combine like terms: -8x + -10x = -18x -106 + -18x = 20 + 10x + -10x Combine like terms: 10x + -10x = 0 -106 + -18x = 20 + 0 -106 + -18x = 20 Add '106' to each side of the equation. -106 + 106 + -18x = 20 + 106 Combine like terms: -106 + 106 = 0 0 + -18x = 20 + 106 -18x = 20 + 106 Combine like terms: 20 + 106 = 126 -18x = 126 Divide each side by '-18'. x = -7 Simplifying x = -7
| -2-3x=13-8x | | 11x+25=146 | | 6x-12=48 | | 34x-4=14 | | x^4+4x^3+6x^2+4x-15=0 | | -m(3m+14+mn)= | | 2x-15=45 | | 6x+25=14x-55 | | 34x-4=114 | | 34x-4=11 | | X-25=-17 | | 11x-8=5x+20 | | q-2p=-2 | | (3x+-4)(7x+19)(3x+3)= | | 3p+4q=36 | | X+15=24 | | 3a+2a+8=23 | | 4(1+n)=-4 | | 4w+x=2w+7 | | 5-3*(4+5x)=-67 | | 8x+(-7-5x)+10=18 | | m=8 | | 8t+12=-2t+32 | | y=x^2-10x+11 | | 3u+7=2u-10 | | 4x+3x^2-5=0 | | 6(x^2)-x-15=0 | | 0=x^2-2x+1 | | x^2-3x+10=20 | | 9x+3y=3 | | 3b-7=0 | | 3ax+3b+2=3x+5 |